Separation and Estimation of Split “Products” of Fibrinogen and Fibrin in Human Serum - Niléhn, J. E (Thrombosis and Haemostasis, 1967)
Pure fibrinogen and fibrinogen in plasma respectively, were digested with plasmin under various conditions. The split products obtained were afterwards separated on Sephadex G 200 and determined immunologically. The investigation showed that when plasmin digested plasma is separated by gel filtration high molecular weight split products with antigenic determinants for both D and E products occur in at least 3 different main types, which are eluted in the “19 S” and “7 S” peaks. On digestion of pure fibrinogen investigated in the same way only 2 main types of split products occurs in the same region. In the “4 S” peak D and E products occur as end degradation products.The amount of split products formed in serum samples with fibrinolysis is larger than in those with fibrinogenolysis.Split products in sera from patients with different diseases were identified after gel filtration on Sephadex G 200. As a rule, they were eluted together with the macro - globulins (“19 S”) but samples from patients with advanced fibrinolytic conditions were also found to have split products of lower molecular weight, which were eluted later in the “7 S” and “4 S” peaks.With the immunologic technique used split products in the serum can be determined down to a concentration of 0.5 mg/100 ml. Split products were found in a concentration between 1 and 45 mg/100 ml in certain patients with liver disease, blood disease, cancer and thrombosis, but not in any of the healthy subjects studied.